Viral pseudoenzymes in infection and immunity. (17th September 2020) - Wang, Ting‐Yu; Zhao, Jun; Savas, Ali Can; Zhang, Shu; Feng, Pinghui
Abstract : Pseudoenzymes are proteins that are evolutionarily related to active enzymes, but lack relevant catalytic activity. As obligate intracellular pathogens, viruses complete their life cycle fully dependent on the cellular supplies of macromolecule and energy. Traditionally, studies of viral proteins sharing high homology with host counterparts reveal insightful mechanisms by which host signaling pathways are delicately regulated. Recent investigations into the action of cellular pseudoenzymes elucidate diverse molecular means how enzymes are differentially controlled under various physiological conditions, hinting to the potential that pathogens may exploit these regulatory modalities. To date, there have been three types of viral pseudoenzymes reported and our understanding concerning their mechanism of regulation is rudimentary at best. However, it is clear that viral pseudoenzymes are emerging with surprising functions in infection and immunity, and we are only at the beginning to understand this new group of enzyme regulators. In this review, we will summarize current knowledge in viral pseudoenzymes and provide a perspective for future research. Abstract : Viral pseudoenzymes are represented by enzyme‐deficient homologs of glutamine amidotransferase (GAT), kinase, and superoxide dismutase that modulate the signaling output in immune defense, viral genome replication, and cell proliferation, respectively. Specifically, pseudo‐GAT cooperates with a cellular GAT to enable deamidation; pseudo‐SOD competes with cellular SODs for chaperoned‐copper to cripple dismutase activity; and pseudokinase pairs with viral and cellular kinases to balance the phosphorylation of key signaling molecules (e.g., BAF).